Solubilities of CO2 in aqueous N-methyldiethanolamine and guanidinium trifluoromethanesulfonate ionic liquid systems at elevated pressures - Sairi, Nor Asrina; Yusoff, Rozita; Alias, Yatimah; Aroua, Mohamed Kheireddine (Elsevier, 2011)
In this work, the solubility of CO2 in aqueous blended systems of N-methyldiethanolamine (MDEA) and guanidinium trifluoromethanesulfonate ([gua]+[OTf]−) have been carried out. The solubilities were measured at temperature 303.2 K, 323.2 K and 333.2 K, over CO2 partial pressure ranging from 500 to 3000 kPa. All data were reported as loading capacity (mol CO2/total mol) as a function of partial pressure of CO2 at the corresponding temperature. It has been found that the aqueous [gua]+[OTf]− ionic liquid gave significantly higher solubility, up to 1.63 mol CO2/total mol, as compared to other pure ionic liquids such as [bmim]+[BF4]−, [emim]+[OTf]− and [emim]+[C2N3]− which recorded at 323.2 K and 3000 kPa. However, the addition of [gua]+[OTf]− ionic liquid to aqueous MDEA gave a slight decreased on solubility. Correlations of solubility as a function of partial pressure and temperature were obtained with deviation of ±0.957%.